Identifikasi dan Uji Patogenisitas Penyebab Penyakit Hawar Daun Pada Suren (Toona sureni Merr.) - Achmad; Maisaroh, Mamay (Institut Pertanian Bogor (IPB University), 2004)
Rhizoctonia sp. causes leaf blight on Toona sureni. This pathogen has characteristics such as right-angles hyphal branching pattern, the presence of septa, the absence of clamp connection, produced no conidia nor spores, and formed sclerotia. The disease symptom is necrotic type with brownish lesions which develop fast on the leaf. Being covered by the lesions, the leaf will be completely brown, macerated and then become wilt, dry and fall. The dispersal of the disease is mediated by the touching of the infectious leaves with the healthy ones. The experiment showed that Rhizoctonia inoculation on leaf, with or without wound, caused the seedling diseased.